'Femminicidio' in Italy: A critique of feminist gender discourse and constructivist reading of the human identity. (November 2016) - Bandelli, Daniela; Porcelli, Giorgio
In recent years a feminist gender discourse of femicide has become established in Italian political debate. Stereotypical and sexist representations of women are singled out as key issues to be addressed in the fight against Violence Against Women (VAW). Gender discourse and associated cultural/linguistic enterprise simplify heterosexual (violent) relational dynamics, overshadow different situational, relational and socio-psychological readings of violence and foreground a cultural understanding of the human being as a self-determined artificially constructed identity. The authors of this article suggest that this discourse on femicide can be read through the lens of Foucault's theory of biopolitics, as a device of manipulation of human identity. Furthermore the authors borrow from Habermas's theory of public sphere and argue that the hegemonic gender interpretation of femicide reflects the specific vantage point of feminist groups while it is not the result of any inclusive public reflections on the causes of this social phenomenon. Their core argument is that a gender discourse of femicide contributes to the advancement of a social constructivist paradigm in the interpretation of self in postmodern society, a society that, as warned by sociologist David Riesman and Jungian psychologist Tony Wolff, is populated by individuals that conform to cultural values.